TUHAN DAN RUNTUHNYA TEMBOK ARGUMENTASI - Putu Dana Yasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Human efforts to understand the existence of God have been proven by the emergence of various arguments about God. Philosophers and theologians have contributed their thoughts in an effort to explain God. However, it must be admitted honestly, that every argument presented still has weaknesses that directly have not been able to define God in a final way. The arguments that arise have not been able to explain God that can be universally accepted, this of course must be acknowledged because of the limitations of humans who try to explain God without limits. The arguments presented by experts are proof that God is still a big mystery that has not been revealed by humans. The existence of God is still a debate between existence and non-existence, although the evidence for its existence is undeniable.